Iplementasi Strategi Mimicrymemorization pada Pembelajaran Mufradat Bahasa Arab bagi Siswa Madrasah Ibtidaiyahmin 7 Bandar Lampung - Koderi Koderi; Erni Zuliana; Arif Budiman (Institut Agama Islam Negeri Metro, 2021)
Abstract This research was motivated by the difficulty and weakness of the Ibtidaiyah students' mastery of mufradat in learning Arabic. The formulation of the application